Peramalan Jumlah Penderita Jenis Penyakit Utama Di Kota Surabaya Menggunakan Metode Autoregressive Integrated Moving Average (ARIMA) - Tri Diana Rimadhani; Amalia Anjani Arifiyanti; Rizka Hadiwiyanti (Student Research Journal, 2023)
The decline in Covid-19 pandemic cases over the past few months before 2023 not only reduced Indonesia's challenges in dealing with other types of diseases. Surabaya city itself has health issues that need to be addressed, as indicated by an increase in several diseases in 2022. One attempt to handle disease cases is to predict the future case numbers to anticipate actions early on. By using data on the number of cases of Respiratory System Diseases during the year 2022, this data will be used to predict the number of cases in the coming months in 2023 by creating a variation of a univariate ARIMA forecasting model. Therefore, the research results show forecasted data that tend to increase when viewed from the analysis and the plotted graph of the forecast results.